INTERNAL AND EXTERNAL ANALYSIS IN BUILDING SUSTAINABLE COMPETITIVE ADVANTAGE IN SULSELBAR BANK MAROS BRANCH - Aldo Barik Risal; Abdul Rahman Kadir; Nuraeni Kadir (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
The competitive conditions in the banking sector are also getting tougher, especially with the onset of the era of free trade today, companies must exercise a sustainable competitive advantage which can be seen from the extent to which the company is able to unite various activities that match each other, making the company different and unique from its competitors so as to continuously outperform them. This study aims to analyze the internal and external conditions in SWOT Analysis, as well as to determine the strategy used by PT. Bank Sulselbar Maros Branch in building a competitive advantage in a sustainable manner. Data collection techniques through observation, questionnaires, and documentation. While the data analysis technique used SWOT analysis. The results of the study found that the results of the analysis of internal conditions and external conditions at PT. Bank Sulsebar, Maros Branch, show that in a SWOT analysis the strengths and opportunities are greater than the weaknesses and threats faced. This means that the position of PT. Bank Sulselbar Maros branch has been in an advantageous position thus encouraging aggressive growth policy. Determination of a suitable strategy used by PT. Bank Sulsebar, Maros Branch in building a sustainable competitive advantage is a market penetration strategy, namely a growth strategy by increasing market share in the marketing of bank service products, increasing market growth by expanding the bank's product marketing network to remote areas in order to add new customers.